Analysis of adverse drug reactions reported in a Tertiary care hospital - VARSHA RAMESH; VASANTHI.C; DARLING CHELLATHAI DAVID (International Journal of Pharma and Bio Sciences, 2017)
Adverse Drug Reactions (ADRs) are an important cause of morbidity and mortality all over the world. This study aims at collecting and analysing Adverse Drug Reactions in a tertiary care hospital. This is a retrospective observational study, done at Sri Ramachandra Medical College Hospital, a tertiary care hospital over a period of 6 months. These ADRs were reported by the medication safety team of our hospital in CDSCO ADR forms of PvPI. The collected ADRs were subjected to WHO causality assessment scale by Pharmacology department. The causalities and other aspects of the ADRs were analysed in detail by us. A total of 118 ADRs were reported during this study period. Antibiotics contributed to the maximum number of ADRs which accounted for 67.80% of the total, followed by Analgesics and Iron containing preparations which accounted for 8.5% of the total ADRs. Causality assessment of ADRs by WHO scale showed that maximum reactions were categorized as Probable (61.86%) followed by the possible category (34.74%). The most common mode of presentation was itching followed by pruritic rash. One case of Norfloxacin induced Steven Johnson Syndrome was reported. One case of reaction to Iomeron contrast dye was also reported. Antimicrobial classes of drugs contributed to the maximum causative agents for ADRs, followed by analgesics and Iron containing preparations. Steroids, Ranitidine and Cardiovascular drugs contributed to a small percentage of ADRs during this period. The majority of ADRs were probable on WHO assessment scale.